Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 192936 by Abdullahrussell last updated on 31/May/23

Answered by Frix last updated on 31/May/23

Obviously x^2 =3∨x^2 =4 ⇒  x=±(√3)∨x=±2  If we use ((−z))^(1/3) =−(z)^(1/3)  also x^2 =12 ⇒ x=±2(√3)

Obviouslyx2=3x2=4x=±3x=±2Ifweusez3=z3alsox2=12x=±23

Answered by MM42 last updated on 31/May/23

(√(x^2 −3))=u⇒x^2 =u^2 +3  ⇒u+((1−u^2 ))^(1/3) =1⇒1−u^2 =(1−u)^3   ⇒u(u−1)(u−3)=0  ⇒u=0⇒x^2 =3⇒x=±(√3)  & u=1⇒x^2 =4⇒x=±2  & u=3⇒x^2 =12⇒x=±2(√3)

x23=ux2=u2+3u+1u23=11u2=(1u)3u(u1)(u3)=0u=0x2=3x=±3&u=1x2=4x=±2&u=3x2=12x=±23

Commented by MM42 last updated on 31/May/23

the diagram below shows the state[  of the threads  f(x)=(√(x^2 −3))+((4−x^2 ))^(1/3) −1

thediagrambelowshowsthestate[ofthethreadsf(x)=x23+4x231

Commented by MM42 last updated on 31/May/23

Terms of Service

Privacy Policy

Contact: info@tinkutara.com